REGULATION OF PATENT RIGHTS AS AN OBJECT OF FIDUCIARY GUARANTEE - I Made Bagus Bhismananda; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The aim of this research is to understand the regulation of patent rights as an object of fiduciary guarantee and to know and understand the process of executing patent rights as an object of fiduciary guarantee. The type of research used is normative legal research using a statutory approach and a conceptual approach. The result of this research is that the regulation of patent rights as an object of fiduciary guarantee is regulated in the provisions of Article 108 paragraph (1) of the Patent Law. Furthermore, related to the process of executing patent rights as an object of fiduciary guarantee, it refers to the Patent Law. Patent rights cannot be sold at public auction. The patent rights execution process can be carried out through the transfer of patent rights with a written agreement outlined in the form of a notarial deed, which must then be registered and announced through the Director General of Intellectual Property Rights. The economic value attached to the patent can be used by creditors to pay off debtors' debts.